Assessing Rural Community Empowerment through Community Internet Centre: Using Asset Mapping and Surveys Method - Ab Halim, Amirah; Mohd Noor, Marhaini (JOIV : International Journal on Informatics Visualization, 2023)
This paper assesses community empowerment through Community Internet Centre. Community empowerment is a process of the outcome made by the community to take action and change or improve the community's quality of life. Hence, adopting Information and Communication Technology would bridge the digital divide in rural areas. The digital divide affected rural community development through numerous barriers that widened the gap between urban and rural communities, consequently generating an imbalance in community development. The community internet center can bridge the digital divide among urban and rural communities. Asset mapping and surveys have been measured to assess rural community empowerment dimensions through distributed questionnaires to eight Community Internet Centres in rural areas of Kelantan. The findings indicate that the Internet Centre is a medium to encourage community empowerment. The Internet Centre bridges the digital divide among communities by providing Information and Communications Technology community building in rural areas. Hence, the center drives community empowerment and improves the quality of life in rural communities. Thus, Community Internet Centre prepared an appropriate platform for empowering the rural community. This is evidence based on the outcome of findings which resulted in three domains of community empowerment: (1) community participation, (2) ownership, and (3) information services. Nevertheless, community participation determined the outcomes of the roles played by the center to empower a community. Further study needs to be conducted in other groups of samples and gaining other perspectives from managerial of the internet center to get different views of the internet center program.